A three-step dissociation method for converting Xiaolongtan lignite into soluble organic compounds: Insights into chemicals, geochemical clues, and structural characteristics. (15th April 2019) - Liu, Fang-Jing; Zong, Zhi-Min; Li, Wei-Tu; Zhu, Xiang-Nan; Wei, Xian-Yong; Tang, Ming-Chen; Huang, Zai-Xing
Graphical abstract: Abstract: Converting lignite into soluble organic compounds (SOCs) under mild conditions is significant for both evaluating molecular structure and producing clean fuels/chemicals. A three-step dissociation, i.e., sequential extraction, sequential thermal dissolution (TD), and ruthenium-ion-catalyzed oxidation (RICO), was adopted to convert the organic matter (OM) in Xiaolongtan lignite (XL) into SOCs. The perspectives on chemicals, geochemical information, and structural characteristics of XL were evaluated based on the molecular compositions of SOCs. Much higher yields of SOCs were obtained from TD than from extraction, which could be attributed to the thermal dissociation of non-covalent interactions in XL. Normal alkanes, alkyl-substituted benzenes, alkyl-substituted phenols, ketones, and aliphatic esters are the main group components released from TD. A series of important biomarkers were released and their distributions and evolution pathways during XL-forming process imply that higher terrestrial plants could be the main input of the OM in XL. Benzenecarboxylic acids were produced from TD residue in high selectivity via the RICO. According to the results from the RICO, the insoluble macromolecular structures in XL are rich in peri-condensed aromatics along with some cata -condensed aromatics and polyaryls, and CH3 is the major alkyl side chain on the aromatic rings. Adjacent aromatic moieties are mainly connected each other directly by Car Car bridged bonds.